Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1/ 10(X-7)-8(X+5)=6(-5)+24
10x - 70 - 8x - 40 = -30 +24
2x - 110 = -6
2x = 104
x=52
2/ 8(X-|-7|)-6(X-2)=|-8|.6-50
8(x - 7) - 6(x-2) = 8.6 - 50
8x - 56 - 6x +12 =48 -50
2x - 44 = -2
2x = 42
x=21
3/ 2(4X-8)-7(3+X)=|-4|(3-2)
8x-16 - 21 - 7x = 4.1
x-37=4
x=41
4/ 12(X-4)=6(x-2)-16(X+3)=7|-4|
12x - 48 = 6x - 12 - 16x -48 =7.4
12x - 48 = 28
12x=76
x=19/3
5/ 4(X-5)-7(5-X)+10(5-X)=-3
4x - 20 -35 +7x + 50 -10x = -3
x - 5 = -3
x = -2
Chúc bạn học tốt!
1) (-6-2)*(-6+2)=-8*(-4)=32
2) (7*3-3):(-6)=18:(-6)=-3
3) (-5+9)*(-4)=4*(-4)=-16
4) 72:(-6*2+4)=72:(-8)=-9
5) -3*7-4*(-5)+1=-21-(-20)+1=-21+20+1=0
6) 18-10:(+2)-7=18-5-7=6
7) 15:(-5)*(-3)-8=9-8=1
8) (6*8-10:5)+3*(-7)=48-2-21=25
( 1+2+3+4-1-2-3-4) * 1*2*...........*8*9
= 0 * 1*2*...........*8*9
= 0
2) -3(4 - 7) + 5(-3 + 2)
= -3.4 + 3.7 - 5.3 + 5.2
= -12 + 21 -15 + 10
= 31 - 27
= 4
4) -5(2 - 7) + 4(2 - 5)
= -5.2 + 5.7 + 4.2 - 4.5
= -10 + 35 + 8 - 20
= 38 - 30
= 8
(5^7+7^5).(6^8+8^6).(2^4-4^2)
=(5^7+7^5).(6^8+8^6).(16 - 16)
=(5^7+7^5).(6^8+8^6) . 0
= 0